2019
DOI: 10.1039/c9lc00075e
|View full text |Cite
|
Sign up to set email alerts
|

Integrated elastomer-based device for measuring the mechanics of adherent cell monolayers

Abstract: We developed an integrated device for measuring the Young's modulus of adherent cell monolayers over time within a physiological environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 46 publications
2
4
0
Order By: Relevance
“…This suggests that MDCK cell bodies contribute more to the monolayer stiffness than the ECM and basement membrane proteins. Our results are in agreement with those by Sorba et al , 41 who showed that in MDCK monolayers, the cell covered region had a higher relaxation time constant (10.09 ± 1.42 s −1 ) than the bare PDMS region (3.18 ± 1.47 s −1 ), via tensile testing, and that EDTA treated MDCK cells had a lower Young's modulus (6.86 ± 3.27 kPa) than untreated cells (23.3 ± 6.3 kPa).…”
Section: Resultssupporting
confidence: 94%
“…This suggests that MDCK cell bodies contribute more to the monolayer stiffness than the ECM and basement membrane proteins. Our results are in agreement with those by Sorba et al , 41 who showed that in MDCK monolayers, the cell covered region had a higher relaxation time constant (10.09 ± 1.42 s −1 ) than the bare PDMS region (3.18 ± 1.47 s −1 ), via tensile testing, and that EDTA treated MDCK cells had a lower Young's modulus (6.86 ± 3.27 kPa) than untreated cells (23.3 ± 6.3 kPa).…”
Section: Resultssupporting
confidence: 94%
“…Then as a result, lower cellular Young's modulus were observed Teixeira et al (2003). Note that the Young's modulus of MDCK cells measured in this study 4-40 kPa is in agreement with previously reported values Sorba et al (2019). Furthermore, the lower contractility of the cells on the structured substrates leads to lower shear stress of the cells Mollaeian et al (2018b); .…”
Section: Resultssupporting
confidence: 91%
“…There has also been development of open-source stretchers [13,19,18,20,24] to make the cell stretching systems more accessible. Recently, there have been developments of cell stretchers that also allow for force measurements [22]. For example, the deformation of a silicone sheet has been used to approximate the elastic module of a cell layer [22].…”
Section: Hardware In Contextmentioning
confidence: 99%